The impact on usage of social media on academic Performance among university students in Sabah – a conceptual paper - Haslinda Hasan; Lai Che Ching; Intan Soliha Ibrahim; Syahruddin Awang Ahmad; Aisah Meri (Global Academic Excellence, 2022)
This is a conceptual paper that attempts to show that social media can improve the academic performance of university students. The study assumes that it is interesting to investigate the impact of social media on university students' academic performance, given the explosion in the number and use of social media sites worldwide. In addition, social media offers new opportunities to engage learners and teachers and can also be used in face-to-face, blended and e-learning settings. This paper highlights the benefits of using social media for effective communication between lecturers and students, and students and fellow students during the online teaching and learning process. Interestingly, the literature in this area also highlights the benefits and risks of using social media in teaching and learning. The findings of the study will also be useful for academics, researchers and policy makers in the context of innovations in teaching and learning